The Future of Medical Device Regulation Innovation and Protection - Glenn Cohen, I.; Minssen, Timo; Nicholson Price II, W.; Robertson, Christopher; Shachar, Carmel (Social Sciences, 2022)
As the nature of medical devices is rapidly changing, the legal and ethical questions around medical devices are becoming ever more complex. This volume analyses the current issues and controversies around patient privacy, innovation, and new regulatory laws in the US and EU.